2017
DOI: 10.1097/tp.0000000000001798
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Circulating Leukocytes and Pyroptosis During Ex Vivo Lung Perfusion Improves Lung Preservation

Abstract: Our data demonstrated that circulating leukocytes derived from donor lungs, and not circulating proinflammatory cytokines substantially impaired the quality of lung grafts through caspase-1-induced pyroptotic cell death during EVLP. Removing these cells with a LF and/or inhibiting pyroptosis of the cells can be a new therapeutic approach leading to long-term success after lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…Recent studies have demonstrated the accumulation of inflammatory cytokines during MP, attributed to release by tissue resident leukocytes. (7,8) Moreover, graft cells injured during the ischemia/reperfusion (I-R) process release various damage-associated molecular patterns (DAMPs) into the perfusate. (9) DAMPs are a heterogeneous collection of molecules released by injured and dying cells that bind to distinct pattern-recognition receptors on tissue resident leukocytes and graft cells, initiating proinflammatory responses.…”
Section: Original Article | 611mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the accumulation of inflammatory cytokines during MP, attributed to release by tissue resident leukocytes. (7,8) Moreover, graft cells injured during the ischemia/reperfusion (I-R) process release various damage-associated molecular patterns (DAMPs) into the perfusate. (9) DAMPs are a heterogeneous collection of molecules released by injured and dying cells that bind to distinct pattern-recognition receptors on tissue resident leukocytes and graft cells, initiating proinflammatory responses.…”
Section: Original Article | 611mentioning
confidence: 99%
“…Recent studies have demonstrated the accumulation of inflammatory cytokines during MP, attributed to release by tissue resident leukocytes . Moreover, graft cells injured during the ischemia/reperfusion (I‐R) process release various damage‐associated molecular patterns (DAMPs) into the perfusate .…”
mentioning
confidence: 99%
“…In addition, recipient T cell infiltration of the donor lung was significantly diminished in the study group (158). In another study by Noda et al, the role of circulating leukocytes in lungs and their relationship with circulating pro-inflammatory cytokines on ischemia-reperfusion injury was investigated in a rat lung transplant model (159). Lung function was significantly better in lung grafts on EVLP with a leucocyte filter in the circuit compared to a control group without.…”
Section: Lungmentioning
confidence: 88%
“…It is well established that PMNs recruited within the lung allograft represent crucial cellular effectors of PGD . PMNs within the transplanted lungs may arise from two distinct sources, the first one being the donor lung itself, which possesses an important reservoir of marginated neutrophils, forming highly toxic NETs (neutrophil extracellular traps) and being immediately recruitable upon transplantation, and the second one being the circulating PMNs from the recipient . The latter pool of PMNs infiltrate the graft upon interaction between leukocyte‐derived integrins with selectins and adhesion molecules expressed by the endothelium in the donor lung .…”
Section: Discussionmentioning
confidence: 99%